Audit IT Process "Me-01" on Academic Information Systems Using Cobit 4.1 (Case Study on Some Vocational Higher Education) - Surya, Rendra Trisyanto; Sudjana (Jurnal Multidisiplin Madani, 2024)
In Vocational Universities, where the density of theoretical and practical lectures is so high, the role of AIS becomes more crucial. However, AIS, which is driven by Information Technology, is often evaluated irregularly and with inappropriate means, methods or approaches as the level of technological complexity increases. Even though Information Technology Governance (IT Governance) is a necessity for me-scale organizations, it also has immature management and governance processes. Here then, Monitoring and Evaluation of Academic Information Systems (AIS) carried out using a traditional-conventional approach no longer provides maximum results. COBIT then became the framework of choice in many industries, including universities. COBIT is starting to be widely used to manage (managerial) and at the same time measure (audit) the performance of Information Technology, including Information Systems. COBIT creates a work reference (Framework) through High-Level Control Objectives and Detailed Level Control Objectives for each IT Process, including IT Process ME-01. referring to IT Process Me-01 COBIT. However, on the other hand, the desire to improve and improve AIS performance appears to be very high, namely 3.8, which means Defined. Awareness of the importance of Information Technology in the process of implementing the Tri Dharma of Higher Education and maintaining the quality of AIS is recognized as the key to success in managing higher education today. Only the majority of leaders at various levels do not understand how to implement COBIT